Aphicidal Activity of Illicium verum Fruit Extracts and Their Effects on the Acetylcholinesterase and Glutathione S-transferases Activities in Myzus persicae (Hemiptera: Aphididae). Issue 1 (30th January 2016) - Zhou, Ben-Guo; Wang, Sa; Dou, Ting-Ting; Liu, Su; Li, Mao-Ye; Hua, Ri-Mao; Li, Shi-Guang; Lin, Hua-Feng
Abstract: This study aims to explore the aphicidal activity and underlying mechanism of Illicium verum Hook. f. that is used as both food and medicine. The contact toxicity of the extracts from I. verum fruit with methyl alcohol (MA), ethyl acetate (EA), and petroleum ether (PE) against Myzus persicae (Sulzer), and the activities of acetylcholinesterase (AChE) and glutathione S-transferases (GSTs) of M. persicae after contact treatment were tested. The results showed that MA, EA, and PE extracts of 1.000 mg/l caused, respectively, M. persicae mortalities of 68.93%, 89.95% and 74.46%, and the LC50 of MA, EA, and PE extracts were 0.31, 0.14 and 0.27 mg/l at 72 h after treatment, respectively; the activities of AChE and GSTs in M. persicae were obviously inhibited by the three extracts, as compared with the control, with strong dose and time-dependent effects, the inhibition rates on the whole reached more than 50.00% at the concentration of 1.000 mg/l at 72 h after treatment. The inhibition of the extracts on AChE and GSTs activities (EA extract > PE extract > MA extract) were correlated with theirs contact toxic effects, so it is inferred that the decline of the metabolic enzymes activities may be one of important reasons of M. persicae death. The study results suggested that I. verum extracts have potential as a eco-friendly biopesticide in integrated pest management against M. persicae.